Pengembangan Critical Thinking melalui Penerapan Model PBL (Problem Based Learning) dalam Pembelajaran Sains - Widowati, Asri (MAJALAH ILMIAH PEMBELAJARAN, 2010)
This paper examines to explore how study by using model of Problem Based Learning ( PBL). Basically, this discussion is focussed at model of PBL as an effort in developing cognitive ability, especially critical thinking.Critical thinking including ability think high level (higher order of thinking) representing one of the component in issue intellegence of 21 st century ( Issue of The 21st literacy century). Development of ability of critical thinking in study of science of vital importance because the ability used in so many human life aspect. The alternative model study of which can develop ability of critical thinking is Problem Based Learning (PBL)